The Role of Mediation of Work Motivation in Determining Working Readiness of Vocational School Students - Galih Rakasiwi, Putra; Sukardi, Thomas; Indra, Muhammad; Aldo, Jefri (Universitas Pendidikan Ganesha, 2023)
The competency of vocational high school students is still said to be lacking in work readiness. This is caused by a lack of encouragement for oneself, family, school facilities, school environment, etc. This research aims to analyze the mediating role of work motivation in determining vocational school students' work readiness. This research uses an ex-post facto quantitative approach with the path analysis method. Research subjects in 3 vocational schools in machining engineering expertise in class XII with a total sample of 193 people. Data collection uses questionnaires, interviews, and documentation. Hypothesis testing in this study used SmartPLS 3 software. The findings show that work competency and industrial work practice experience can influence work motivation. Work motivation can directly influence students' work readiness. Indirectly, work competency affects work motivation through work readiness. Indirectly, industrial work practice experience affects work motivation through work readiness. It was concluded that work motivation plays a role in determining vocational school students' work readiness, especially in class XII machining engineering, followed by work competency and industrial work practice experience. So it is recommended to the vocational school community always to be motivated so that students are ready to work, have sufficient competence and experience, and always pay attention to the 3 things researchers discovered and discussed because vocational schools aim to work, continue, and become self-employed.